REKONSTRUKSI PEDIDIKAN ISLAM DAN PERAN PESANTREN DALAM MEMBANGUN KEPRIBADIAN MUSLIM YANG KAFFAH - Mohamad Mundzir; Isnawati Nur Afifah Latief (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
Resource development is indeed quite basic as a target human development with all its physical and mental devices. Absorption natural resources and the environment without including source development human power, will result in the growth of excessive exploitation. Even will damage the environment, will also destroy potential sources for humanity's prosperity. But keep in mind that source development human power cannot be separated from community social development. Because what it means is the abundance of natural resources, without a form of society harmonious. Morally how it involves social spirituality in managing their social environment by utilizing existing resources. So the Islamic boarding schools must be more open and flexible in seeing social reality, nature and the environment and its institutional system, with all progress and the development of science and technology in practice must be able to educate and prepare qualified human resources in accordance with the demands of the times. In the life of the Islamic boarding schools there are values, ethos and culture in fact, it is very appropriate to develop a noble attitude. The values developed are for example: the values of monotheism, humanity, justice and honesty, concern for other beings, independence and unity and others. Islamic boarding schools with ethos that are carried, do good deeds according to the needs and aspirations of the community. On the basis of the aims of guiding and maintaining harmony, boarding schools appear and grow without waiting and hoping for rewards from anyone. This is what later gave birth to a large number of Islamic boarding schools with all their strengths and limitations